Influence of Temperature Upon Permanent Deformation Parameters of Asphalt Concrete Mixes (Journal of Engineering, 2017)
The performance of asphalt concrete pavement has affected by many factors, the temperature is the most important environmental one which has a large effect on the structural behavior of flexible pavement materials. The main cause of premature failure of pavement is the rutting, Due to the viscoelastic nature of the asphalt cement, rutting is more pronounced in hot climate areas because the viscosity of the asphalt binder which isinversely related to rutting is significantly reduced with the increase in temperature resulting in a more rut susceptible paving mixtures. The objective of this study is to determine the effect of temperatures variations on the permanent deformation parameters (permanent strain (p), intercept (a), slope (b), Alpha and Mu) as well as   resilient strain (r) and resilient modulus (Mr). To achieve this objective, one aggregate gradation with 12.5mm nominal maximum size, two grades of asphalt cements (40-50 and 60-70) brought form Al- Daurah refinery, limestone dust filler has been used to prepare the asphalt concrete mixtures. 30 Marshall specimens were prepared to determine the optimum asphalt cement content. Thereafter, 30 cylindrical asphalt concrete specimens (102mm in diameter and 203 mm in height) are prepared in optimum asphalt cement and optimum ±0.5 percent. The prepared specimens were used in uniaxial repeated load test to evaluate the permanent deformation parameters of asphalt concrete mixes under the following testing temperature (5, 15, 25, 40 and 60c). The test result analyses appeared that Mr is decrease 51 percent when temperature increased from 5 c to 25 c and then decrease 22 percent with further increase in temperature from 25 c to 60 c. Also, the Alpha value decreases by a factor of 1.25 and 1.13 when temperature increases from 5 c to 25 c and 25 c to 60 c, espectively. Finally, statistical models were developed to predict the Alpha and Mu  parameters of permanent deformation.